Migration and Its Impact on Sustainable Development - Muslih Faozanudin; Shainima Islam (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2021)
People’s mobility and international migration are quite interesting phenomena to discuss. Until now, there are still differences in views between industrialized countries and developing countries regarding the contribution of migration to development for both sending and receiving countries. This paper aims to analyze based on existing secondary data the linkage between migration and sustainable development. For analysis, this study uses a descriptive approach, with secondary data as the primary source. The analysis found that both sending and receiving countries - benefited from population mobility and international migration. The least developed countries in the economy and overall infrastructure are supplying countries for this migration process, and increasing remittances and skilled workers to help other countries. Although it is realized that this condition is the impact of the weak economic system of developing countries on the one hand and the demographic that occur in advanced industrialized countries on the other. To maintain the stability of the supply chain for economic development, international migration is included as one of the sustainable development programs that apply more humane values. Therefore, migrants should be seen as potential contributors to the growth of sending and receiving countries, and some even claim that they are heroes of foreign exchange. Keywords: migration, remmitance, sustainable development Mobilitas masyarakat dan migrasi internasional merupakan fenomena yang cukup menarik untuk dibahas. sampai saat ini masih terdapat perbedaan pandangan antara negara industri dan negara berkembang, tentang kontribusi migrasi terhadap pembangunan, baik bagi negara yang asal migrant maupun bagi negara penerima. Makalah ini bertujuan untuk menganalisis berdasarkan data sekunder yang ada mengenai keterkaitan antara migrasi dan pembangunan berkelanjutan. Untuk analisis, penelitian ini menggunakan pendekatan deskriptif, dengan data sekunder sebagai sumber primer. Hasil analisis menemukan bahwa kedua negara-negara pengirim dan penerima - mendapat manfaat dari mobilitas penduduk dan migrasi internasional. Negara-negara kurang berkembang dalam ekonomi dan infrastruktur secara keseluruhan menjadi negara pemasok untuk proses migrasi ini, dan meningkatkan pengiriman uang dan pekerja terampil untuk membantu negara lain. Meskipun disadari bahwa kondisi ini merupakan dampak dari lemahnya sistem perekonomian negara berkembang di satu sisi dan faktor demografi dan kesuburan yang terjadi di negara industri maju di sisi lain. Untuk menjaga stabilitas rantai pasokan pembangunan ekonomi, migrasi internasional dimasukkan sebagai salah satu program pembangunan berkelanjutan yang menerapkan nilai-nilai yang lebih manusiawi. Oleh karena itu, para migran harus dilihat sebagai kontributor potensial bagi pertumbuhan negara pengirim dan penerima, bahkan ada yang mengklaim bahwa mereka adalah sebagai pahlawan devisa. Kata kunci: migrasi, pembangunan berkelanjutan, remiten